Korelasi Antara Human Development Terhadap Anggaran Pertahanan Negara Menurut GDP - Endro Tri Susdarwono; Firman Sani (Jurnal Wira Ekonomi Mikroskil, 2023)
Human development is one of the important factors in economic growth. Qualified human resources have high productivity so as to be able to increase the efficiency of economic activity and in the aggregate can affect economic growth. This study aims to describe the relationship between human development and the size of a country's defense budget allocation. This research approach uses descriptive quantitative based on hypothesis testing based on the method of testing hypotheses through chi-square distribution. Through this method, independent variables and dependent variables which consist of several categories are displayed in a table. then, a series of procedures and calculations must be carried out and test criteria must be formulated to determine the null hypothesis status. This study concludes that there is a correlation between human development and a country's defense budget. The correlation value between the two variables is 36.30%.